2021
DOI: 10.1111/mpp.13073
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas arboricola pv. juglandis and pv. corylina: Brothers or distant relatives? Genetic clues, epidemiology, and insights for disease management

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 102 publications
(274 reference statements)
0
31
0
Order By: Relevance
“…gardneri, X. perforans and X. vesicatoria) still require several steps-observation of disease symptoms, microscopic examination, pathogen isolation, pathogenicity tests and molecular tests [27][28][29][30][31][32][33][34]. Having in mind that only recently X. euroxanthea was proposed as a new species [4], isolated from different plant hosts [7][8][9][10], for which the nature of the bacteria-plant interaction is still unknown, and no distinct symptoms have been described [4], the herein proposed multiplex PCR is the tool available for accurate detection and identification of X. euroxanthea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…gardneri, X. perforans and X. vesicatoria) still require several steps-observation of disease symptoms, microscopic examination, pathogen isolation, pathogenicity tests and molecular tests [27][28][29][30][31][32][33][34]. Having in mind that only recently X. euroxanthea was proposed as a new species [4], isolated from different plant hosts [7][8][9][10], for which the nature of the bacteria-plant interaction is still unknown, and no distinct symptoms have been described [4], the herein proposed multiplex PCR is the tool available for accurate detection and identification of X. euroxanthea.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, apart from its occurrence in walnuts (Juglans regia), recent evidence was gathered reporting the isolation of X. euroxanthea from distinct plant host species, such as Carya illinoensis (pecan; strains CPBF 761 and CPBF 766), that together with walnut (Juglans regia; strains CPBF 367, CPBF 424 T , CPBF 426 and CFBP 7653) belong to the Juglandaceae family; Solanum lycopersicum (tomato plants; strains BRIP 62409, BRIP 62411, BRIP 62415 and BRIP 62418) a member of the Solanaceae family [7][8][9]; and Phaseolus vulgaris (common bean; strain CFBP 7622, previously misclassified as X. arboricola [10,11]), a Fabaceae plant species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting disease susceptibility on the different species was assessed using the percentage of seedlings with cankers on the stems and branches. In a recent review, Kałuzna et al (2021) highlighted the similarities between Xac and Xaj suggesting that inoculation, identification, and management techniques successful on Xaj could also be informative if applied on Xac. The time saved by using this spray inoculation technique would allow for greater population sizes and could be incorporated into mass bacterial blight screening on hazelnut.…”
Section: Discussionmentioning
confidence: 99%
“…(Miller et al, 1940). Bacterial blight symptoms are found on leaves, buds, twigs, trunks, and occasionally nuts, primarily on young hazelnut trees between 1 and 4 years old (Miller et al, 1949;Scortichini et al, 2002;Lamichhane and Varvaro, 2014;Kałuzna et al, 2021). It has been shown that Xac may reside epiphytically on asymptomatic plant tissues including under bud scales for extended periods without inducing symptoms (Pisetta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%